Hip osteoarthrosis: clinical presentation, diagnosis, approaches to treatment - Marina Stanislavovna Svetlova (Современная ревматология)
The paper characterizes the specific features of the anatomy and physiology of the hip joint, the clinical presentation of coxarthrosis and presents current methods for the diagnosis and treatment of the disease. It gives the results of a trial evaluating the impact of long-term (one-year) theraflex therapy on the symptoms of hip osteoarthrosis.